(untitled) (Bangladesh Medical Journal, 2020)
Solitary papilloma in the respiratory tract is a rare benign epithelial tumor which is complete surgical excision of the current standard treatment for this type of tumor. Here a case of solitary tracheal papilloma treated by surgical resection is reported. Due to rarity and non-specific symptoms, tracheal papilloma always subjected to misdiagnosed and suffer from delayed treatment. In this case, a forty two years male has been presented with a recurrent non-productive irritative cough, a progressive shortness of breath, expiratory stridor and occasional hemoptysis. The patient was previously diagnosed as a case of bronchial asthma by a Pulmonologist and wrongly treated as well. CT scan revealed an intraluminal tracheal mass arises from the right side of the tracheal wall opposite c6-c7 vertebrae. The tumour was removed by endoscopic excision. The histopathological result confirms the diagnosis of squamous cell papilloma. No complications occur during surgery and no recurrence was observed in six months after surgery on followup. Bangladesh Med J. 2020 May; 49(2) : 44-47